Potential of Professional Thinking and Emotional Burnout in the Professions of Socionomic Type - I.V. Serafimovich (Moscow State University of Psychology and Education, 2023)
The analysis of specific features of professional thinking and emotional exhaustion among teachers and doctors in the context of COVID-19 pandemic. The growing demand for practical social psychological support of members of “person to person” professions during the unstable epidemiological situation due to COVID-19 have preconditioned the consideration of emotional exhaustion in the terms of interconnection with professional thinking that is able to contribute new professional and personal meaning to the activity process, thus becoming the cognitive resource that balances the levels and components of emotional exhaustion. The method of content analysis and expert evaluation alongside with mathematical statistical methods, such as correlation method of Charles Spearman and Student’s t-distribution, were used. Participants: 55 people, the members of professions of socionomic type, 25 teachers and 30 doctors, length of time worked – 10-25 years, men – 30%, women – 70%. The methods of studying the specific features of emotional exhaustion (V.V. Boyko; Christina Maslach, S. Jackson, adapted by N.E. Vodopiyanova) and components of professional thinking (the author’s method of self-analysis of the problem situation by I.V. Serafimovich and M.M. Kashapov). It has been demonstrated that suprasituatedness of thinking is negatively correlated with emotional burnout, while situatedness is positively correlated with it. It has been specified that the emotional burnout is more pronounced in doctors. It has been identified that adequacy and sufficiency of analysis of a problem situation are positively associated with the self-esteem of professional success and self-satisfaction, whereas validity is associated with the capability to cope with psychologically destructive circumstances. Under the high efficiency of analysis emotional involvement reduces, and when increasing the depth of analysis emotional burnout enhances. The obtained results about the partial connection of components of professional thinking and signs of emotional exhaustion can be used as the arguments for the author’s position of the ability of usage of thinking as a cognitive resource for solving practical problems.